"Zinā" and Gender (In)Equality in Ismāʿīlī Druze Law - Halawi, Wissam H. ca. 20./21. Jh. (Der Islam, 2022)
In the 5th/11th century in Cairo, Imam Ḥamza, the founder of the Druze faith, abrogated the entire substantive laws, including the Islamic one. And yet, four centuries later, Druze jurists in the mountainous regions of Syria developed their own legal doctrine. This essay explores the evolution of Druzism from an esoteric doctrine according to the Ismāʿīlī vision to a madhhab (doctrinal school of law) using the prism of gender (in)equality. Through a close reading of the Imam’s epistles in the Ḥikma (i.e., the Druze canon of scripture) and Druze law treatises from the 9th/15th century, I show how premodern Druze jurists were influenced particularly by Shāfiʿī and Mālikī law. Although they remained faithful to the strict gender equality articulated in their sacred book, Druze jurists established a gender hierarchy in marriage and permitted wife beating based on Q 4:34. They however expounded an original doctrine of zinā (adultery): despite their construction of femininity as inferior and irrational, and their assumption of women’s intellectual deficiency, Druze jurists considered nonconsensual marriage as well as nonconsensual sex in marriage to be crimes of zinā . I argue that Druze jurists developed rules that enforced sexual equality but simultaneously conformed to their patriarchal vision of society to maintain the social cohesion of their religious community, clans, and extended families, all of which provided local networks for informal conflict resolution.